Polemik Pencatatan Anak Dari Nikah Siri - Agus Manurung; Lusia Sulastri (Jurnal Hukum Sasana, 2021)
The current unregistered married couple can have a new KK provided that the data for the Statement of Absolute Responsibility (SPTJM) form refers to Permendagri No. 9/2016 concerning the Acceleration of Increasing the Coverage of Birth Certificate Ownership. The SPTJM document itself consists of two things. First, the SPTJM of the Truth of Birth Data made by biological parents/guardians/applicants with full responsibility for the correctness of a person's birth data with the knowledge of two witnesses. Second, the SPTJM Truth as a Married Couple made by the biological parents/guardians/applicants with full responsibility for the status of a person's marital relationship with the knowledge of two witnesses. The registration of children from unregistered marriages through a Statement of Absolute Responsibility (SPTJM) refers to Permendagri No. 9/2016 concerning the Acceleration of Increasing the Coverage of Birth Certificate Ownership still causes legal problems, non-fulfillment of marriage certificates/marriage certificate quotations and family relationship status in KK that do not show marital relationship status as husband and wife, then the data recorded in the child's birth certificate quote is only only his mother's name. Not at the same time include the name of the father as in a legal marriage. So that the child still needs to prove who the father is if needed in the future. Apart from that, there will be many obstacles in the effort to prove because the existence of a new KK through the SPTJM document has weak evidentiary power because it is limited to one-sided acknowledgment of the signatories. As well as other obstacles deliberately caused by the litigants. The position of Siri's own wife is very vulnerable to legal protection as well. In the absence of legal status as a legal wife, there has not been a reciprocal legal relationship of rights and obligations as a married couple. The fulfillment of the rights and obligations of each cannot use the basis of the demands for fulfillment of the law but is only limited to the stages of good faith by each party.